2022
DOI: 10.1038/s41531-022-00355-2
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson’s disease-associated, sex-specific changes in DNA methylation at PARK7 (DJ-1), SLC17A6 (VGLUT2), PTPRN2 (IA-2β), and NR4A2 (NURR1) in cortical neurons

Abstract: Evidence for epigenetic regulation playing a role in Parkinson’s disease (PD) is growing, particularly for DNA methylation. Approximately 90% of PD cases are due to a complex interaction between age, genes, and environmental factors, and epigenetic marks are thought to mediate the relationship between aging, genetics, the environment, and disease risk. To date, there are a small number of published genome-wide studies of DNA methylation in PD, but none accounted for cell type or sex in their analyses. Given th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 98 publications
(100 reference statements)
3
40
0
1
Order By: Relevance
“…Considering that the incidence of PD in men is nearly twice that in women, it was unexpected that more DNAm changes were found in the blood of female patients (69 CMRs) than male patients (2 CMRs) and at similar magnitudes in the TERRE sample 64 . However, this was consistent with a recent sex-stratified EWAS in the parietal cortex of PD patients where 3 PD-associated CpGs were reported in men, and 87 in women 49 . Similarly, it was somewhat surprising that pesticide exposure, and in particular low-dose exposure, contributed to CMR model fit in females, considering that male TERRE subjects had higher levels of pesticide exposure (i.e., occupational).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Considering that the incidence of PD in men is nearly twice that in women, it was unexpected that more DNAm changes were found in the blood of female patients (69 CMRs) than male patients (2 CMRs) and at similar magnitudes in the TERRE sample 64 . However, this was consistent with a recent sex-stratified EWAS in the parietal cortex of PD patients where 3 PD-associated CpGs were reported in men, and 87 in women 49 . Similarly, it was somewhat surprising that pesticide exposure, and in particular low-dose exposure, contributed to CMR model fit in females, considering that male TERRE subjects had higher levels of pesticide exposure (i.e., occupational).…”
Section: Discussionsupporting
confidence: 92%
“…Lastly, sex differences in routes of exposure (e.g., household vs. occupational pesticide use) and mechanisms of exposure (e.g., bio-accumulation in adipose tissue) are often present and may or may not be reflected in exposure measurement 46 48 . However, most genetic and epigenetic studies of PD to date have opted to control for sex as a covariate rather than examining sex-specific aspects of PD etiology, with the exception of a recent sex-stratified EWAS in post-mortem brain 10 , 12 , 14 , 15 , 24 , 25 , 29 , 49 .…”
Section: Introductionmentioning
confidence: 99%
“…5(f)). In the literature, PLXNB3 is linked with neuronal axon guidance by regulating cell adhesion and is differentially methylated in male PD patients 62 parietal cortex; CYP27A1 catalyses the conversion of cholesterol into bile acids and has low serum concentrations in PD and other neurodegenerative diseases; 63 ECI2, ADH5 and CBR1 catalyses fatty acid metabolism and have been previously linked with PD and aging; 64,65 ALDH1B1 is linked with lipid peroxidation; ALDH9A1 catalyses gamma aminobutyric acid metabolism; ALDH7A1 protects cells from oxidative stress and its variants have been associated with female PD patients in Taiwan; 66 and L1CAM modulates nervous system development and synaptic plasticity and can be used as a potential diagnostic marker for PD. 67 Altogether, our study proposes a new set of metabolic alterations, which are consistent with current knowledge in the literature, in the human brain which might be important for PD drug research and diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…At the clinical level, the symptoms, course of the disease, and the response to medication are also influenced by sex (Bakeberg et al, 2021; Gillies et al, 2014; Haaxma et al, 2007). A recent study has demonstrated that the DNA methylation profile of several core genes of PD pathology is sex specific (Kochmanski et al, 2022). The susceptibility to environmental neurotoxicity in PD patients has also been demonstrated to be associated with sex (Adamson et al, 2022).…”
Section: Brain Lipid Changes: Effect Of Sex On Neurodegenerative Dise...mentioning
confidence: 99%
“…Less than 10% of the cases are identified as familial origin (Bloem et al, 2021). However, the majority of cases are the result of the complex interplay among several factors, such as age, genetics and epigenetics, environmental influence, and sex (Kalia & Lang, 2015; Kochmanski et al, 2022; Obeso et al, 2017).…”
Section: Brain Lipid Changes: Effect Of Sex On Neurodegenerative Dise...mentioning
confidence: 99%